2016
DOI: 10.1193/012414eqs016m
|View full text |Cite
|
Sign up to set email alerts
|

Full-Scale Structural and Nonstructural Building System Performance during Earthquakes: Part I – Specimen Description, Test Protocol, and Structural Response

Abstract: A landmark experimental program was conducted to advance the understanding of nonstructural system performance during earthquakes. The centerpiece of this effort involved shake table testing a full-scale five-story reinforced concrete building furnished with a broad variety of nonstructural components and systems (NCSs) including complete and operable egress, mechanical and electrical systems, facades, and architectural layouts. The building-NCS system was subjected to a suite of earthquake motions of increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 25 publications
(33 reference statements)
2
75
0
Order By: Relevance
“…Periods of 2.0 and 3.15 s were the lowest and highest periods calculated for the BI building, as discussed later. These values were found using data from GPS stations on the foundation level and data from Temposonics displacement sensors attached to the actuators below the platen, and differ only slightly from values inferred from accelerometer data [26]. Note that the spectral displacements listed in Tables I and II were computed for the equivalent viscous damping ratios assumed in design of the building for the design earthquake: ζ = 12% for the BI configuration and ζ = 5% for the FB configuration.…”
Section: Building Description and Test Programmentioning
confidence: 79%
See 2 more Smart Citations
“…Periods of 2.0 and 3.15 s were the lowest and highest periods calculated for the BI building, as discussed later. These values were found using data from GPS stations on the foundation level and data from Temposonics displacement sensors attached to the actuators below the platen, and differ only slightly from values inferred from accelerometer data [26]. Note that the spectral displacements listed in Tables I and II were computed for the equivalent viscous damping ratios assumed in design of the building for the design earthquake: ζ = 12% for the BI configuration and ζ = 5% for the FB configuration.…”
Section: Building Description and Test Programmentioning
confidence: 79%
“…For the BI configuration, the displacement response spectra for tests motions BI1, BI2, BI3, and BI5 were similar in the period range of interest. There were two additional motions that took the FB structure well into the inelastic range that are not considered in this paper [26,27]. Test motion BI4 had greater spectral displacements than those in test motions BI1, BI2, BI3, and BI5 over the entire period range of interest, but contrary to the spectral displacement trend in these three test motions, the spectral displacement of test motion BI4 generally decreases with an increase in period.…”
Section: Building Description and Test Programmentioning
confidence: 99%
See 1 more Smart Citation
“…This publication is available free of charge from: https://doi.org/10.6028/NIST.GCR.17-917-44 Figure 6-3 Measured building response in the longitudinal direction: (a) peak floor accelerations during the base isolated tests; (b) peak interstory drift ratios during the base isolated tests; (c) peak floor accelerations during the fixed base tests; and (d) peak interstory drift ratios during the fixed base tests (Chen et al, 2015).…”
Section: -8 6: Simulated Seismic Testing Of Gcr 17-917-44 Nonstructumentioning
confidence: 99%
“…6 Similarly, extensive damage to NCSs in different facilities was reported after the 2011 off the Pacific coast of Tohoku earthquake, 7 and even in some cases, the loss of human life had been attributed to falling ceiling boards. Chen et al 9 and Pantoli et al 10 reported on a series of 1D shaking experiments on a full-scale, 5-story reinforced concrete building, conducted at the University of California, San Diego (UCSD) NEES site (NEES@UCSD). Recent Network for Earthquake Engineering Simulation (NEES) projects have focused on system-level response evaluation of NCSs on full-scale shake table experiments, to better understand their performance under seismic excitation.…”
mentioning
confidence: 99%